Flow Experiences in Physical Education Classes: The Role of Perceived Motivational Climate and Situational Motivation - ADA, Elif Nilay; ÇETİNKALP, Zisan Kazak and ALTIPARMAK, M.Ersin and AŞÇI, F.Hülya (Asian Journal of Education and Training, 2018)
The purpose of this study was to determine the role of perceived motivational climate and situational motivation levels on dispositional flow in physical education classes. 242 boys (Mage=13.38; SD=0.95) and 251 girls (Mage=13.27; SD=0.88) a total of 493 secondary school students (Mage=13.32; SD=0.91) voluntarily participated in this study. Physical Education Situational Motivational Scale, Learning and Performance Orientation in Physical Education Classes Questionnaire and Physical Education Dispositional Flow Scale-2 were administered to all participants. Hierarchical regression analysis indicated that identified regulation, intrinsic motivation, pupil learning climate and teacher-initiated learning explained a significant amount of variance in dispositional flow in physical education (p<0.05). The pupil learning climate, identified regulation and leisure time sport participation were the strongest predictors, respectively. These findings suggested that promoting mastery-oriented climate, self-determined situational motivation, and participation in sport will foster dispositional flow in the physical education setting.